CGIAR Initiative on NEXUS Gains at the 9th Asian Regional Conference on Irrigation and Drainage - Alam, Mohammad Faiz; Sikka, Alok (International Water Management Institute (IWMI). CGIAR Initiative on NEXUS Gains, 2024)
IWMI organized two international workshops at the 9th Asian Regional Conference on irrigation and drainage in Sydney, Australia in September 2024. Supported by NEXUS Gains, the two sessions covered the importance of the water–energy–food–ecosystems (WEFE) nexus for the irrigation sector, and irrigation modernization to build resilience and adapt to climate change.